PENGARUH PENGHARGAAN TERHADAP KINERJA KARYAWAN MELALUI LOYALITAS PADA PT. BANGUN CIPTA ANUGRAH ABADI PALEMBANG - Safira, Bella; Rismansyah, Rismansyah; Kurbani, Adie (Universitas Nusa Cendana, 2024)
This study aims to determine the effect of Rewards on Employee Performance through Loyalty to PT. Bangun Cipta Anugrah Abadi Palembang. The population in this study were all employees of PT. Bangun Cipta Anugrah Abadi Palembang, totaling 103 employees. The type of research used is quantitative research. Data analysis techniques in this study employed validity and reliability tests, hypothesis testing, and path analysis techniques using the SPSS 22 Windows program. The results of the discussion show that the first research hypothesis test proved that Rewards have a direct effect on Employee Performance, the second research hypothesis test proved that Rewards have a direct effect on Loyalty, the third hypothesis test proved that there is a direct significant effect of Loyalty on Employee Performance, and the fourth hypothesis test proved that indirectly Rewards for Employee Performance have a significant influence on Loyalty. Keywords: Rewards; Employee Performance; Loyalty